Critical Thinking Technology in the Training of Law Professionals - Mohammad Anwar, Mohammad Sarwar (2021)
According to the Federal State Educational Standards of Secondary Vocational Education (FSES SVE), graduates should master general and professional competencies according to the specialty. Students should acquire a certain set of knowledge and skills and gain practical experience in accordance with the Federal State Educational Standard through the study of professional modules. The professional modules are subdivided into interdisciplinary courses. In practice, the challenges in the educational process of secondary vocational education are in the development of general competencies. General competencies include the ability to apply acquired knowledge, skills and practical experience in solving general problems in a wide field of activity. Professional competency is the ability to apply the knowledge, skills and experience gained in solving professional problems in particular activities. The competency-based approach corresponds to the demands of society and employers for specialists capable to apply knowledge in practice, to independently set tasks and solve them in specific situations. Based on the foregoing, the technology for the development of critical thinking is able to satisfy the needs of teachers and students in the conditions of a competency-based approach. The development of thinking skills and abilities of students in the educational process is necessary not only during vocational training or in professional activity, but also in everyday life. This is especially important in the unstable economic and political situation in the Russian Federation and the world at the present time, when it is necessary to quickly, sometimes even radically reorganize their career under the prevailing circumstances. A specific feature of the educational process of secondary vocational education is not only a competency-based approach to learning, but also a modular approach implemented through professional modules. Professional modules and interdisciplinary courses included in them are defined by the FSES SPE, however, in some cases, the variability of the content of the module is allowed, i.e. the educational institution independently decides which interdisciplinary courses to include in the module.